Utilize Renewable Energy Kits to Develop Students' Lower and Higher-Order Thinking Skill - Yennita*, Yennita; Zulirfan, Zulirfan; Sarkity, Dios; Agustin, Dita Safrina; Iksan, Zanaton H (Jurnal Pendidikan Sains Indonesia, 2024)
This research aims to determine the effect of kits renewable energy projects by implementing a project-based learning model on students' lower order thinking skills (LOTS) and higher order thinking skills (HOTS). The research method used was quasi-experimental with a nonequivalent posttest only control group design. The population in this study was 198 students. Samples were taken randomly from a population that had passed the normality test and homogeneity test. This research uses a cognitive learning outcomes test instrument in the form of multiple choices. The research results show that there is no significant difference in cognitive learning outcomes in the LOTS category between students in classes that apply project-based learning on renewable energy material and classes that apply conventional learning on renewable energy material, sig. 0.127 0.05, using the Mann Whitney test. Meanwhile, the results of hypothesis testing for cognitive learning outcomes in the HOTS category using the independent sample t-test obtained a sig (2-tailed) value of 0.000 0.05, which means there is a significant difference in students' cognitive learning outcomes. between classes that apply project-based learning to renewable energy material and classes that apply conventional learning to renewable energy material. These results indicate that project-based learning can produce student learning in the HOTS category, but has no effect on increasing students' cognitive abilities